Use of the fresh groundwater for the cities water supply: current state of affairs and prospects - I. S. Zektser (Известия высших учебных заведений: Геология и разведка, 2016)
A brief description of the role of fresh groundwater in drinking water supply of large cities of Russia and the comparative evaluation of groundwater resources and the use of groundwater for various purposes in Russia and the United States are given. Land subsidence under the influence of large groundwater withdrawal is characterized. The assessment of the possibility of the fresh groundwater use for the urban water supply in emergency situations, both in current conditions as well as a forecast for the 2030, is given. On the basis of existing needs for drinking water and the availability of approved groundwater resources, the approximate prediction of groundwater supply for cities is made for different emergency situations. Possible changes in the population of cities and established water consumption rates are taken into account. The conclusion about the necessity of creation of a backup system of water supply based on fresh groundwater protected from contamination is justified.